Analysis of User Acceptance of the Academic Information System at Universitas 17 Agustus 1945 Samarinda Using the Technology Acceptance Model (TAM) Method - Achmad jaya adhi Nugraha; Muhammad Zulfariansyah (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
This study uses the Technology Acceptance Model (TAM) to analyse how well Universitas 17 Agustus 1945 Samarinda's Academic Information System is received by the general public. Academic administration and the quality of services provided to students and faculty are both greatly enhanced by the use of information technology in today's higher education institutions. This study delves deep into the elements that influence users' attitudes, behavioural intentions, and actual system utilisation, specifically examining the impact of perceived utility and perceived ease of use. Academic Information System users at Universitas 17 Agustus 1945 Samarinda were surveyed using questionnaires to gather data. In addition, the data was examined in order to determine the connections between the TAM framework variables. In order to help the university improve service quality and create a more effective, efficient, and user-oriented system, this research is anticipated to explain the level of user acceptability of the academic information system. Additionally, this study has the potential to be a reference for future research on the topic of educational technology adoption.